Floodplain schools in the Para Amazon: a study based on a center in the municipality of Óbidos-PA - Juliana Figueira Nogueira; Anselmo Alencar Colares (Revista Brasileira de Educação do Campo)
The article analyzes the material and pedagogical organization of floodplain schools in response to river floods and dry seasons, focusing on institutions within the Ipaupixuna hub, in Óbidos-PA, which operate through a process of nucleation—that is, the grouping of students and resources around a central or hub school. The research was conducted through document analysis of laws, decrees, the political-pedagogical project, and photographs, as well as secondary sources obtained from educational platforms and the social media account of one of the schools studied. These sources were enriched by prior ethnographic experience, grounded in the extended case study method. The analysis revealed that nucleation leads to the closure of small schools, increasing the travel distance for students and teachers, and further exacerbating the precariousness of teaching work and school management. The schools face poor infrastructure conditions, worsened by floods that cause the deterioration of school buildings. The findings indicate that floodplain schools face specific challenges, particularly due to the environmental conditions they endure. There is a clear need for specific educational policies, with continuous investment and measures to address these conditions, as neoliberal policies tend to intensify existing problems, undermining the educational work carried out in these schools.